2001
DOI: 10.1104/pp.126.1.210
|View full text |Cite
|
Sign up to set email alerts
|

Altered Middle Lamella Homogalacturonan and Disrupted Deposition of (1→5)-α-l-Arabinan in the Pericarp ofCnr, a Ripening Mutant of Tomato

Abstract: Cnr (colorless non-ripening) is a pleiotropic tomato (Lycopersicon esculentum) fruit ripening mutant with altered tissue properties including weaker cell-to-cell contacts in the pericarp (A.J. Thompson, M. Tor, C.S. Barry, J. Vrebalov, C. Orfila, M.C. Jarvis, J.J. Giovannoni, D. Grierson, G.B. Seymour [1999] Plant Physiol 120: 383-390). Whereas the genetic basis of the Cnr mutation is being identified by molecular analyses, here we report the identification of cell biological factors underlying the Cnr texture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
107
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(113 citation statements)
references
References 51 publications
5
107
0
1
Order By: Relevance
“…The Cnr tomato mutant shows a disrupted deposition of (1/5)-a-L-arabinan, a modified HG network with reduced calcium-binding capacity in the middle lamellae, and a reduced cell adhesion concomitant with a failure to swell (Orfila et al, 2001(Orfila et al, , 2002. A similar phenomenon is observed in the arabinan-rich walls of Commelina guard cells, in which the wall shape can be frozen open or closed by digestion of 5-linked arabinans (Jones et al, 2003).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The Cnr tomato mutant shows a disrupted deposition of (1/5)-a-L-arabinan, a modified HG network with reduced calcium-binding capacity in the middle lamellae, and a reduced cell adhesion concomitant with a failure to swell (Orfila et al, 2001(Orfila et al, , 2002. A similar phenomenon is observed in the arabinan-rich walls of Commelina guard cells, in which the wall shape can be frozen open or closed by digestion of 5-linked arabinans (Jones et al, 2003).…”
Section: Discussionmentioning
confidence: 60%
“…In the tobacco (Nicotiana plumbaginifolia) mutant nolac-H14, RG Is with low levels of associated arabinans were not retained in the cells walls and middle lamella (Iwai et al, 2001). The altered HG network and reduced cell adhesion observed in the Cnr tomato mutant could be a consequence of disrupted arabinan deposition in this tomato cell wall (Orfila et al, 2001(Orfila et al, , 2002. A role for arabinans in anchoring pectin in the wall was suggested by these authors, but the decreased abundance and altered location of arabinan side chain when RG I was fragmented in muro by a rhamnogalacturonan lyase in transgenic potato plants indicated that cross-linkage between arabinans and other components of the wall is unlikely (Oomen et al, 2002).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Less attention has been paid to this role for adhesion in plants. By using a variety of approaches, genetic studies have implicated pectins in adhesion (17)(18)(19)(20)(21), but none are as definitive as the Iwai et al 2002 study (5). A very recent report (22) of two dwarf Arabidopsis mutants that have a 25% reduction in galacturonic acid levels is the most intriguing.…”
mentioning
confidence: 99%
“…In the Arabidopsis parvus mutants, characterized by reduced levels of RG-I branching, growth and fertility are influenced by humidity (Lao et al, 2003). The tomato (Lycopersicon esculentum) Cnr mutant has an altered deposition of both HGA and arabinan in the fruit pericarp, affecting cell wall properties and intercellular adhesion (Thompson et al, 1999;Orfila et al, 2001). …”
mentioning
confidence: 99%